2014
DOI: 10.1080/14786419.2014.902947
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid content and radical scavenging potential of extracts prepared from tobacco cultivars and waste

Abstract: The flavonoid-rich natural products exert a wide range of pharmacological properties. This investigation aimed at obtaining extracts from tobacco cultivars and waste enriched with flavonoids and purified from nicotine and phenolic acids, and evaluating their radical scavenging potential. Extraction with a mixture of ethyl acetate-methanol (1:1, v/v) was employed resulting in 100% yield for flavonoids and 36% yield for phenolic acids. The crude extracts were purified using preparative column chromatography on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 15 publications
3
9
0
1
Order By: Relevance
“…Regardless of tobacco type, Wang et al [27] also reported that the dominant polyphenols in tobacco leaves were chlorogenic acid and rutin. Similar profile was also found in Virginia and Oriental tobaccos [66] and in light air-cured (Burley) tobacco [67]. Chlorogenic acid and rutin contents in both light air-cured (Burley) and dark fire-cured (Ken-tucky) tobacco of our experiment were comparable to that reported for other kind of tobacco (Oriental) [68] or for some medicinal species [69].…”
Section: Phenolic Profile: Phenolic Acids and Flavonoidssupporting
confidence: 88%
“…Regardless of tobacco type, Wang et al [27] also reported that the dominant polyphenols in tobacco leaves were chlorogenic acid and rutin. Similar profile was also found in Virginia and Oriental tobaccos [66] and in light air-cured (Burley) tobacco [67]. Chlorogenic acid and rutin contents in both light air-cured (Burley) and dark fire-cured (Ken-tucky) tobacco of our experiment were comparable to that reported for other kind of tobacco (Oriental) [68] or for some medicinal species [69].…”
Section: Phenolic Profile: Phenolic Acids and Flavonoidssupporting
confidence: 88%
“…Popova et al [21] reported significant amounts of other phenolic compounds in tobacco extracts, like salicylic, proto–catechuic, and p–Coumaric acid. Moreover, Docheva et al [9] reported that with an increase of flavonoid content in tobacco and tobacco waste extracts, the antioxidant activity of extracts also increased. However, tobacco leaves contain carotenoids such as lutein, P–carotene, neoxanthin, and violaxanthin, which also might affect antioxidant activity [45].…”
Section: Resultsmentioning
confidence: 99%
“…The cassava leaf flavonoid extract then was tested using liquid chromatography-tandem mass spectrometry (LC-MS/ MS) to determine the level of flavonoid. The procedure was based on a modification of two different protocols proposed by Docheva et al and Muhammad et al 10,11 The extract was altered into gel at the Laboratory of Pharmaceutical Faculty of Pharmacy, Universitas Jember. The manufacturing process of gel base was started with carbopol developed in hot water in a mortar, and then stirred until homogeneous before added with triethanolamine (TEA) in small increments until gel mass was formed.…”
Section: Methodsmentioning
confidence: 99%